Thermally triggered hydrogel injection into bovine intervertebral disc tissue explants induces differentiation of mesenchymal stem cells and restores mechanical function. (May 2017) - Thorpe, A.A.; Dougill, G; Vickers, L.; Reeves, N.D.; Sammon, C.; Cooper, G.; Le Maitre, C.L.
Graphical abstract: Abstract: We previously reported a synthetic Laponite® crosslinked pNIPAM-co-DMAc (L-pNIPAM-co-DMAc) hydrogel which promotes differentiation of mesenchymal stem cells (MSCs) to nucleus pulposus (NP) cells without additional growth factors. The clinical success of this hydrogel is dependent on: integration with surrounding tissue; the capacity to restore mechanical function; as well as supporting the viability and differentiation of delivered MSCs. Bovine NP tissue explants were injected with media (control), human MSCs (hMSCs) alone, acellular L-pNIPAM-co-DMAc hydrogel or hMSCs incorporated within the L-pNIPAM-co-DMAc hydrogel and maintained at 5% O2 for 6 weeks. Viability of native NP cells and delivered MSCs was maintained. Furthermore hMSCs delivered via the L-pNIPAM-co-DMAc hydrogel differentiated and produced NP matrix components: aggrecan, collagen type II and chondroitin sulphate, with integration of the hydrogel with native NP tissue. In addition L-pNIPAM-co-DMAc hydrogel injected into collagenase digested bovine discs filled micro and macro fissures, were maintained within the disc during loading and restored IVD stiffness. The mechanical support of the L-pNIPAM-co-DMAc hydrogel, to restore disc height, could provide immediate symptomatic pain relief, whilst the delivery of MSCs over time regenerates the NP extracellular matrix; thus the L-pNIPAM-co-DMAc hydrogel could provide a combined cellular and mechanical repair approach. Statement of Significance: Low back pain (LBP) is associated with degeneration of the intervertebral disc (IVD). We have previously described development of a jelly delivery system (hydrogel). This has the potential to deliver adult stem cells to the centre of the IVD, known as the nucleus pulposus (NP). Here, we have demonstrated that adult stem cells can be safely injected into the NP using small bore needles, reducing damage to the disc. Following injection the hydrogel integrates with surrounding NP tissue, promotes differentiation of stem cells towards disc cells and restores IVD mechanical function. The hydrogel could be used to restore mechanical function to the IVD and deliver cells to promote regeneration of the disc as a minimally invasive treatment for LBP.